2008
DOI: 10.1029/2008jb005700
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of polar motion data: Chandler wobble, phase jumps, and geomagnetic jerks

Abstract: We reconsider the analysis of the polar motion with a method totally different from the wavelet analysis used in previous papers. The total polar motion is represented as the sum of oscillating annual and Chandler terms whose amplitude and phase perturbations are inverted with a nonlinear simulated annealing method. The phase variations found in previous papers are confirmed with the huge phase change (≈3π/2) occurring in the 1926–1942 period and another less important one (≈π/3) in the 1970–1980 epoch. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…Both studies showed that these phase jumps appear to be correlated with geomagnetic jerks, and that geomagnetic jerks are followed by phase jumps in the Chandler wobble within at most 3.5 years. These first results have been more recently confirmed (Gibert et al 2008) using different techniques. In this new study, the total polar motion (the combination of the oscillating annual and Chandler terms) amplitude and phase perturbations are inverted with a nonlinear simulated annealing method.…”
Section: Chandler Wobble and Geomagnetic Jerkssupporting
confidence: 78%
See 1 more Smart Citation
“…Both studies showed that these phase jumps appear to be correlated with geomagnetic jerks, and that geomagnetic jerks are followed by phase jumps in the Chandler wobble within at most 3.5 years. These first results have been more recently confirmed (Gibert et al 2008) using different techniques. In this new study, the total polar motion (the combination of the oscillating annual and Chandler terms) amplitude and phase perturbations are inverted with a nonlinear simulated annealing method.…”
Section: Chandler Wobble and Geomagnetic Jerkssupporting
confidence: 78%
“…In this new study, the total polar motion (the combination of the oscillating annual and Chandler terms) amplitude and phase perturbations are inverted with a nonlinear simulated annealing method. Both studies (Gibert et al 1998(Gibert et al , 2008 indicate that a large phase change of around 180 • occurs in the decade after 1926 and another phase change, also remarkable, in the decade after 1970. This last event can be observed in Fig.…”
Section: Chandler Wobble and Geomagnetic Jerksmentioning
confidence: 94%
“…Thus, we do not subscribe to the view that something extraordinary or anomalous had occurred to the Earth system during the 1920s as far as the Chandler phase reversal is concerned (as suspected in, e.g., Bellanger et al, 2002;Gibert and Le Mouël, 2008;Vondrak and Ron, 2005;Malkin and Miller, 2010). The said Chandler phase jump was simply a consequence of the fortuitous small Chandler amplitude at the time; such episodes would occur by chance from time to time, which not surprisingly indeed occurred once during the ∼1 century of observation, a time span comparable to the Q timescale of Chandler wobble.…”
Section: Discussionmentioning
confidence: 82%
“…It helps to judge about the temporal and frequency resolution of corrective smoothing and of Gabor transform used in our work. Gibert and Le Mouel (2008), almost disappears in excitation. This can be explained by the inuence of the dynamical system (1), which introduces π phase shift (see Figure 4b).…”
Section: Chandler Excitation Studymentioning
confidence: 99%